"Because we all love K‐Pop": How young adults reshape symbolic boundaries in Paris, Manchester, and Philadelphia. (9th November 2022) - Cicchelli, Vincenzo; Octobre, Sylvie; Katz‐Gerro, Tally; Yodovich, Neta; Handy, Femida; Ruiz, Stefanie
Abstract: In this paper, we examine how young adults who are consumers of K‐Pop in three culturally diverse cities (Paris, Philadelphia, and Manchester) reshape their symbolic boundaries to face social challenges. Analyzing data from 132 interviews, we show how young adults mainly confront social exclusion in Paris, fight racism in Philadelphia and deal with xenophobia in Manchester. Although K‐Pop adds to the dynamics of exclusion due to being perceived as culturally foreign, our participants use K‐Pop as a resource to reshape social boundaries towards new forms of inclusion. They do this by relying on K‐Pop as a cultural product that promotes inclusion, and on their affiliation with the K‐Pop community on a local and global level.